What Do We Know About the Health Status of Asylum Seekers in the United States?: Identifying Research Gaps Following a Bibliometric Scoping Review of Existing Literature. Issue 2 (24th April 2023) - Beer, Jessica; Dorris, C. Scott; Fateen, Dahlia; Mishori, Ranit
Abstract : Data about US asylum seekers' health are lacking. We assessed the medical literature by performing a bibliometric scoping review of the literature from 1946 to 2020. Of 114 articles identified, 48 (42.1%) were empirical studies and 66 (57.9%) were editorials or commentaries. Empirical studies focused on mental health (60.42%), African asylees (45.83%). Editorials and commentaries focused on detention and medicolegal processes (31.82% and 30.3%). Empirical data on the health of US asylum seekers are limited. Research expansion requires increased commitment, funding, and participatory engagement of asylees. This limited representation in the scientific literature can impact their care and health system preparedness.